2016
DOI: 10.1007/s12275-016-6304-4
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of the antifungal activity of Trichoderma virens 7b and a profile of its non-polar antifungal components released against Ganoderma boninense

Abstract: Ganoderma boninense is the causal agent of a devastating disease affecting oil palm in Southeast Asian countries. Basal stem rot (BSR) disease slowly rots the base of palms, which radically reduces productive lifespan of this lucrative crop. Previous reports have indicated the successful use of Trichoderma as biological control agent (BCA) against G. boninense and isolate T. virens 7b was selected based on its initial screening. This study attempts to decipher the mechanisms responsible for the inhibition of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…An increase of phenolic contents was also observed in soybean when seeds were treated with T. virens (Yusnawan et al 2019). Trichoderma species have been studied for decades as effective bio-control agents against many pathogens through various modes of action (Inayati et al 2020) and these Trichoderma spp., can induce systemic resistance in various plant species and pathogens (Angel et al 2016;Małolepsza et al 2017). The study of Dubey et al (2018) showed that there were upregulated expression of some defense-related genes and catalase in response to the presence of T. virens and R. solani.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of phenolic contents was also observed in soybean when seeds were treated with T. virens (Yusnawan et al 2019). Trichoderma species have been studied for decades as effective bio-control agents against many pathogens through various modes of action (Inayati et al 2020) and these Trichoderma spp., can induce systemic resistance in various plant species and pathogens (Angel et al 2016;Małolepsza et al 2017). The study of Dubey et al (2018) showed that there were upregulated expression of some defense-related genes and catalase in response to the presence of T. virens and R. solani.…”
Section: Discussionmentioning
confidence: 99%
“…racemosus IFO 4581, and A. niger ATCC 6275, while AB204-E (5) and F (6) displayed a positive degree of activity against Gram-positive bacteria, B. subtilis ATCC 6633, K. rhizophila ATCC 9341, M. smegmatis ATCC 607, and S. aureus ATCC 6538p. New antifungal compounds, AB204-A (1) and B (2), possessed similar structures to phenylethyl alcohol (PEA), an antifungal aromatic compound that was obtained from Trichoderma virens 7b, which had significant potential as a biological control agent for BSR [43]. These compounds may exhibit a mechanism in inhibiting fungi similar to PEA which inhibits protein, DNA, RNA, and aminoacyl tRNA syntheses of fungi [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…isobutyl isothiocyanate, dimethyl disulfide, and 2-(methylthio) ethanol, among others), which are highly produced by other antagonistic microorganisms (i.e. Pseudomonas stutzeri E25, Stenotrophomonas maltophilia CR71, and T. virens) (Angel et al, 2016;Rojas-Solís et al, 2018).…”
Section: ----mentioning
confidence: 99%